Evaluating mitophagy in embryonic stem cells by using fluorescence-based imaging - Liu, Kun; Li, Xing; Li, Zheng; Cao, Jiani; Li, Xiaoyan; Xu, Youqing; Liu, Lei; Zhao, Tongbiao (Frontiers in Cell and Developmental Biology, 2022)
Embryonic stem cells (ESCs), which are characterized by the capacity for self-renewal and pluripotency, hold great promise for regenerative medicine. Increasing evidence points to the essential role of mitophagy in pluripotency regulation. Our recent work showed that PINK1/OPTN take part in guarding ESC mitochondrial homeostasis and pluripotency. Evaluating mitophagy in ESCs is important for exploring the relationships between mitochondrial homeostasis and pluripotency. ESCs are smaller in size than adult somatic cells and the mitophagosomes in ESCs are difficult to observe. Many methods have been employed — for example, detecting colocalization of LC3-II and mitochondria — to evaluate mitophagy in ESCs. However, it is important to define an objective way to detect mitophagy in ESCs. Here, we evaluated two commonly used fluorescence-based imaging methods to detect mitophagy in ESCs. By using autophagy- or mitophagy-defective ESC lines, we showed that the mito-Keima (mt-Keima) system is a suitable and effective way for detecting and quantifying mitophagy in ESCs. Our study provides evidence that mt-Keima is an effective tool to study mitophagy function in ESCs.